Williams Syndrome and Music: A Systematic Integrative Review - Thakur, Donovon; Martens, Marilee A.; Smith, David S.; Roth, Ed (Frontiers in Psychology, 2018)
Background: Researchers and clinicians have often cited a strong relationship between individuals with Williams syndrome and music. This review systematically identified, analyzed, and synthesized research findings related to Williams syndrome and music. Methods: Thirty-one articles were identified that examined this relationship and were divided into seven areas. This process covered a diverse array of methodologies, with aims to: 1) report current findings; 2) assess methodological quality; and 3) discuss the potential implications and considerations for the clinical use of music with this population. Results: Results indicate that individuals with WS demonstrate a high degree of variability in skill and engagement in music, presenting with musical skills that are more in line with their cognitive abilities than chronological age. Musical strengths for this population appear to be based more in musicality and expressivity than formal musical skills, which are expressed through a heightened interest in music, a greater propensity toward musical activities, and a heightened emotional responsiveness to music. Individuals with WS seem to conserve the overall structure of musical phrases better than they can discriminate or reproduce them exactly. The affinity for music often found in this population may be rooted in atypical auditory processing, autonomic irregularities, and differential neurobiology. Conclusions: More studies are needed to explore how this affinity for music can be harnessed in clinical and educational interventions.